Iodine contrast exposure and incident COVID-19 infection - Tsai, Karen; Inoue, Kosuke; McClean, Michael; Kaunitz, Jonathan D.; Akiba, Yasutada; Lee, Martin L.; Neverova, Natalia V.; Currier, Jesse W.; Ebrahimi, Ramin; Bashir, Muhammad T.; Leung, Angela M. (Frontiers in Medicine, 2022)
Background: Iodine and particularly its oxidated forms have long been recognized for its effective antiseptic properties. Limited in vitro and in vivo data suggest that iodine exposure may rapidly inactivate, reduce transmission, and reduce infectivity of SARS-CoV-2. We hypothesized that iodine exposure may be associated with decreased incident COVID-19 infection. Methods: A retrospective population-level cohort analysis was performed of the U.S. Veterans Health Administration between March 1-December 31, 2020, before the widespread availability of vaccines against SARS-CoV-2. Multivariable logistic regression models estimated the adjusted odds ratios (OR) and 95% confidence intervals (CI) of the associations between iodinated contrast exposure and incident COVID-19 infection, adjusting for age, sex, race/ethnicity, place of residence, socioeconomic status, and insurance status. Results: 530,942 COVID-19 tests from 333,841 Veterans (mean±SD age, 62.7±15.2 years; 90.2% men; 61.9% non-Hispanic Whites) were analyzed, of whom 9% had received iodinated contrast ≤60 days of a COVID-19 test. Iodine exposure was associated with decreased incident COVID-19 test positivity (OR, 0.75 [95% CI, 0.71-0.78). In stratified analyses, the associations between iodinated contrast use and decreased COVID-19 infection risk did not differ by age, sex, and race/ethnicity. Conclusions: Iodine exposure may be protective against incident COVID-19 infection. Weighed against the risks of supraphysiologic iodine intake, dietary and supplemental iodine nutrition not to exceed its Tolerable Upper Limit may confer an antimicrobial benefit against SARS-CoV-2. A safe but antimicrobial level of iodine supplementation may be considered in susceptible individuals, particularly in geographic regions where effective COVID-19 vaccines are not yet readily available.